126: CLINICAL RELEVANCE OF THE TUMOUR LOCATION-MODIFIED LAURÉN CLASSIFICATION SYSTEM OF GASTRIC CANCER IN A WESTERN POPULATION. (23rd April 2022) - Jonathan, M; Davies, A; Santaollala, A; Van Hemelrijk, M; Maisey, N; Lagergren, J; Gossage, J; Kelly, M; Baker, C
Abstract: Background and aim: The Tumour Location-Modified Laurén Classification (MLC) system of gastric cancer combines Laurén histological subtype and anatomical tumour location. It divides tumours into proximal non-diffuse (PND), distal non-diffuse (DND) and diffuse type. The optimum classification of patients with Laurén mixed tumours within this system is not clear, having been grouped with both diffuse and non-diffuse type in previous studies. The clinical relevance of the MLC has not previously been examined in a Western population. Methods: Cohort study including 404 patients who underwent gastrectomy for gastric adenocarcinoma between 2005–2020. Receiver operating characteristic (ROC) curve analysis was performed to establish the optimal categorisation of Laurén mixed tumours within the MLC when used to predict survival. Survival analysis was performed using Kaplan–Meier and Cox regression. Results: ROC curve analysis demonstrated higher area under the curve (AUC) for predicting overall survival when Laurén mixed tumours were grouped with non-diffuse rather than diffuse type (0.583 vs 0.569). This classification was therefore used for survival analysis. Distal non-diffuse tumours had the best 5-year survival (64.7% DND vs 56.1% PND vs 45.1% diffuse, P = 0.006) and were least likely to have recurrence (27.0% DND vs 34.3% PND vs 48.3% diffuse, P = 0.001). Multivariable analysis demonstrated the MLC was an independent prognostic factor for survival (PND HR 1.64, 95% CI 1.16–2.32, Diffuse HR 2.20, 95% CI 1.56–3.09). Conclusion: The MLC was an independent marker for predicting survival in this Western cohort of patients with gastric adenocarcinoma. Patients with proximal non-diffuse and diffuse tumours had worse survival than those with distal non-diffuse tumours. Table: https://secure.sem-2000.it/semUpload/OLC/file/9203828791100911681076702/94279_Table.jpg .